Restriction Factors in HIV-1 Disease Progression - Merindol, Natacha; Berthoux, Lionel (Current HIV Research, 2015)
About 35 million people worldwide were living with HIV-1 at the end of 2013 and over 25 million have already died of AIDS. AIDS patients show high variability in the speed of disease progression in the absence of treatment. While certain immunological traits have been shown to correlate with accelerated or slowed progression in some subjects, including slow progressors, factors controlling HIV-1 replication and disease kinetics remain largely enigmatic. The importance of T lymphocytes and of protective HLA-alleles is undeniable, but not sufficient to explain every attenuated phenotype. A thorough understanding of HIV-1 infection control in these patient subsets may help the development of novel strategies for treatment and prevention. Restriction factors are type I interferon-induced specialized cellular proteins that block viruses at different steps of their life cycle. TRIM5α, Mx2/MxB, TRIM22/Staf50, SAMHD1, p21/CDKN1, tetherin/BST2/CD137, APOBEC3G and APOBEC3F have all been proposed to inhibit HIV-1, often with gene variant- or cellular context-specificity. Recent evidence highlights their possible implication in AIDS disease progression. In this review, we depict their restrictive activity against HIV-1 and recapitulate the latest data on their potential role in vivo, in both normal and slow progressors.
Keywords: elite controllers